2023
DOI: 10.3390/ijerph20065062
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction among Occupational Therapists Employed in Primary Care Services in Norway

Abstract: The aging population will place healthcare services under considerable strain in the years ahead. Occupational therapists play a vital role in securing sustainable healthcare services and are increasingly employed by municipalities. To promote sustainable services, the job satisfaction among core professional groups needs monitoring. A comprehensive cross-sectional survey was distributed among municipality-employed occupational therapists in Norway during May–June 2022, to which 617 responded. Job satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
3
1
Order By: Relevance
“…described recreation and lifestyle factors such as a slower paced life, boating, beaches and involvement in the community as impactful on job satisfaction. Previous studies have found allied health professionals experience difficulties integrating into communities within rural towns across Australia 14,16 ; however, the Physiotherapists in this study found Kimberley communities easy to embed themselves within and develop close friendships.…”
Section: Discussioncontrasting
confidence: 68%
See 2 more Smart Citations
“…described recreation and lifestyle factors such as a slower paced life, boating, beaches and involvement in the community as impactful on job satisfaction. Previous studies have found allied health professionals experience difficulties integrating into communities within rural towns across Australia 14,16 ; however, the Physiotherapists in this study found Kimberley communities easy to embed themselves within and develop close friendships.…”
Section: Discussioncontrasting
confidence: 68%
“…14 Dimensions range from innate sociodemographic factors through to modifiable factors linked to remuneration, workplace culture, workload and career development opportunities. 11,15,16 These factors coalesce to construct an experience of job satisfaction via intrinsic and extrinsic motivational influences. 14,17 Job satisfaction in the rural and remote health care workforce highlights these extrinsic and intrinsic factors and the complex interplay between workers' professional and personal lives.…”
Section: What This Paper Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…If therapists are supported to adapt to a fuller scope of practice or be involved in determining how to adapt to fill a particular need within a primary care practice, therapists can provide more support for day-to-day primary care services [ 7 ]. Meaningful engagement of primary care therapists in care services planning needs to occur for therapists to have work satisfaction and practice to their optimal abilities [ 47 , 51 ]. This type of planning will also need to consider necessary resources for primary care therapists, so they are not faced with barriers in providing services, as they were during the pandemic with a shortage of technology and support staff to adapt their work roles.…”
Section: Discussionmentioning
confidence: 99%